Aggressions and associations: How workplace violence affects what public employees think of citizens - Marlen C. Liegat; David Hensel; Dominik Vogel; Rick Vogel (Public Administration, 2022)
Scholars have recently spent growing attention to what public employees think of citizens, which influences policy implementation through more manifest attitudes and behaviors. The origins of employees' positive and negative associations with citizens have, however, not been examined thus far. This study draws attention to workplace aggression as critical incidents in state-citizen encounters and examines the traces they leave in employees' subsequent thinking about citizens. Building on social cognition and affective events theory, we hypothesize that the more severe the aggressive incidents have been, the more negative employees' associations with citizens become. Results of a free association task confirm this assumption. Type of work and the gender of the employees moderate the relationship between aggressions and associations. The findings raise awareness for the significance of workplace aggression and provide an outline and agenda of a socio-cognitive theory of public employees' associative thinking about citizens. – – Die aktuelle Forschung beschäftigt sich zunehmend damit, welche Einstellungen Mitarbeiter des öffentlichen Dienstes gegenüber Bürger*innen haben. Woraus positive sowie negative Assoziationen der Mitarbeiter im öffentlichen Dienst mit Bürger*innen resultieren, wurde bisher jedoch nicht erforscht. Diese Studie fokussiert sich auf Aggressionen am Arbeitsplatz als kritische Vorfälle und untersucht deren Auswirkungen auf die Einstellung der Mitarbeiter*innen gegenüber Bürger*innen. Aufbauend auf sozialer Kognition und der Theorie der affektiven Ereignisse stellen wir die Hypothese auf, dass die Assoziationen der Mitarbeiter*innen mit Bürger*innen umso negativer ausfallen, je schwerer die aggressiven Vorfälle waren. Die Ergebnisse einer freien Assoziationsaufgabe bestätigen diese Annahme. Die Art der Arbeit und das Geschlecht der Mitarbeiter moderieren den Zusammenhang zwischen Aggressionen und Assoziationen. Die Ergebnisse sensibilisieren für die Einflüsse von Aggressionen am Arbeitsplatz und liefern einen Entwurf sowie eine Agenda für eine sozial-kognitive Theorie des assoziativen Denkens von Angestellten im öffentlichen Dienst über Bürger*innen.
Keywords: 340